Hand-made Rubber Band Ligater (MUF. - PP Ligater, V1) for Treatment of Hemorrhoids - Phongmanjit, Phichai (Greater Mekong Subregion Medical Journal, 2021)
Background: Symptomatic hemorrhoid are common diseases. Most are grade II to III. Rubber ban ligation is the most effective treatment option. Objective: The aim of the study is to study the efficacy of the hand-made rubber band ligater, PP Ligater, (MUF. - PP Ligater, V1) in treatment grade II to III symptomatic internal hemorrhoid diseases. Methods: We make the hand-made rubber band ligater from the bubble milk tea straws and then use them to treat grade II to III hemorrhoidal diseases. Results: Rubber band ligation were undergone with PP-ligater in 116 procedures. No any complications occur during the period of studying. Conclusions: PP Ligater, (MUF. - PP Ligater, V1) was an acceptable device for grade II to III hemorrhoidal diseases. The hand-made rubber band ligater which made from bubble milk tea straws were used to treat symptomatic grade II to III hemorrhoidal diseases successfully. They made from a cheap material, which easy to make and everyone could make it by oneself.